Fifty years of the Nash program, 1953 - 2003 - Roberto Serrano (Brown University, Department of Economics, 2004)
This paper is a survey of the work in the Nash program for coalitional games, a research agenda proposed by Nash (1953) to bridge the gap between the non-cooperative and cooperative approaches to game theory.
Keywords: C71; C72; C78; 330; Nash program; cooperative games; non-cooperative games; bargaining; implementation; Kooperatives Spiel